Encountered but Not Engaged: Examining the Use of Social Media for Science Communication by Chinese Scientists. (October 2017) - Jia, Hepeng; Wang, Dapeng; Miao, Weishan; Zhu, Hongjun
Thus far, few studies have examined how scientists choose different social media platforms, or how using multiple platforms of social media is related to public engagement with science. This article investigates the role of social media in China's science communication and scientists' selective use of them. We found that social media enabled Chinese scientists to avoid relying on legacy media and to develop more interdisciplinary collaborations. In the process, these scientists strategically chose different social media platforms to increase controllability. Despite their preference for the approach of knowledge dissemination rather than dialogues, Chinese scientists tried to avoid the bureaucratic practice of science communication, and instead, they promoted some level of public participation.